Analysis of the collapse of a greenhouse with vaulted roof. (November 2016) - Briassoulis, Demetres; Dougka, Georgia; Dimakogianni, Danai; Vayas, Ioannis
Abstract : The failure of a multi-span steel greenhouse with vaulted roof covering an area of 7500 m 2 is analysed numerically. Failure occurred during a day of heavy snow and moderate wind. The weather data at the location of the greenhouse and at the time of the collapse were not recorded. Weather data were available from meteorological stations in the broader area though. Numerical models of the complete 3-D structure and of a representative 2-D frame were developed to simulate the greenhouse structural behaviour under various combinations of actions. Linear, geometric and material nonlinear analyses were employed to investigate the causes of collapse. Based on the relevant provisions of the European Standard for greenhouse design and the Eurocodes, loading was varied to allow for an estimation of the real loading conditions at failure. Analysis confirmed the in- and out-of-plane failure modes that were observed after the incident. Based on all available data and the analysis results, it was shown that failure was the result of the combination of many factors that occurred simultaneously: an unfavourable combination of snow and wind actions, the heating system not operating as it should under such weather conditions and the absence of a complete row of internal columns. Highlights: Multi-span greenhouse with vaulted roof collapses under severe weather conditions. Failure mode and damages are assessed and described. Prevailing loading conditions are assessed, actions calculated based on Eurocodes. The collapse mechanism is investigated by means 3-D and 2-D numerical analyses. The critical snow–wind combination and synergic factors at collapse are estimated.